The Croatian Livestock Sector in the Perspective of the New Cap : Pig and Cattle Production Systems, Competitiveness, and Public Expenditure - World Bank (World Bank, Zagreb, 2021)
The European Union’s Common Agricultural Policy (CAP) has evolved since its inception in 1962 and since the expansion of the EU to 28 member countries (EU28 - EU27, since the departure of the United Kingdom on 31 January 2020). In its latest iteration published in June 2018, the 2021-2027 CAP, now due for implementation in 2023, increases environmental sustainability requirements, while offering more flexibility to member state governments. Based on a detailed modelling exercise, consultations with both the Croatian authorities and agricultural stakeholders, this report supports the Croatian authorities in their efforts to comply with new CAP requirements in the livestock subsectors of pigs, beef and dairy production. Specifically, the report addresses two knowledge gaps: production systems, profitability and economic sustainability of production systems; and the effectiveness and equity of public support. The authors examine the main trends in productivity, output, prices, costs, and production technology on which to base their findings. The report also provides a detailed analysis of all types of public support available to livestock farmers, including rural development support, direct coupled and decoupled support, and subsidized diesel fuel, general expenditure on administration, knowledge and education expenditure, subsidized loans. Sections 2-4 include results from the Gap 1 analysis for each of the three subsectors, while section 5 provides a detailed analysis of public expenditure on the livestock sector in Croatia. Section 6 provides an overview of the revised CAP and some potential consequences it may have for the Croatian livestock sector. Policy suggestions are listed in section 7. Section 8 concludes.